A Chronicle Overview of Cephalometric Parameters for assessing Sagittal Jaw Disparity - Dubey, Jaina; Kallury, Amitabh; Balani, Rajesh Kumar; Bharti, Chandni; Dubey, Chandrika (Orthodontic Journal of Nepal, 2021)
Introduction: Assessment of sagittal jaws relation is a vital procedure in establishing a good diagnosis for all orthodontic cases. Various analyses have been introduced over the years with varying degrees of reliability and validity. Orthodontist should be aware of a range of analyses to be used in diagnosing different cases. This review provides a brief information about the various cephalometrics parameters i.e angular & linear which are used for assessing sagittal jaw discrepancy in their chronologic order.